Modulatory effects on dendritic cells by human herpesvirus 6 - Gustafsson, Rasmus; Svensson, Mattias; Fogdell-Hahn, Anna (Frontiers in Microbiology, 2015)
Human herpesvirus 6A and 6B are β-herpesviruses approaching 100% seroprevalance worldwide. These viruses are involved in several clinical syndromes and have important immunomodulatory effects. Dendritic cells (DC) are key players in innate and adaptive immunity. Accordingly, DC are implicated in the pathogenesis of many human diseases, including infections. In this review the effects of HHV-6 infection on DC will be discussed.